2019
DOI: 10.1080/09712119.2019.1643729
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of meat sensory quality, antioxidant status, growth hormone and orexin between Anqingliubai and Yorkshire pigs

Abstract: The pig breeds play an important role in post-mortem meat sensory quality. The aim of this study was to analyse the differences of meat sensory quality, antioxidative ability, growth hormone and orexin between Anqingliubai and Yorkshire pigs. Six Anqingliubai and Six Yorkshire pigs (approximately 100 kg ± 1.5 kg) were slaughtered to assess the longissimus dorsi meat sensory quality, antioxidant ability, serum growth hormone and orexin. Results showed that the Anqingliubai pigs exhibited higher pH, a* and intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Hence, TAC in the blood may be an easy-to-obtain readout which might serve as an indicator of meat color. As such, blood TAC will allow, in the future, the ante-mortem non-invasive screening of animals to determine their cost with regard to meat quality, and possible options to improve it; this probability has already been proposed [65]. However, the present results need to be validated with a larger sample size.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, TAC in the blood may be an easy-to-obtain readout which might serve as an indicator of meat color. As such, blood TAC will allow, in the future, the ante-mortem non-invasive screening of animals to determine their cost with regard to meat quality, and possible options to improve it; this probability has already been proposed [65]. However, the present results need to be validated with a larger sample size.…”
Section: Discussionmentioning
confidence: 90%
“…According to previous research, indigenous Anhui pig breeds exhibit significant differences in meat quality traits and fat deposition capacity compared to commercial pig breeds ( Xu et al, 2018 ; Hu et al, 2019 ; Li et al, 2021 ). In the present study, several genes were found to be associated with fat deposition and other carcass quality traits.…”
Section: Discussionmentioning
confidence: 99%
“…In China, there are more than 80 indigenous pig breeds, constituting a valuable gene bank. The Anqing six-end white pig, an important local pig breed in the province of Anhui in China, has a strong physique, rough feeding resistance, strong stress resistance, and high reproduction rate, and is an ideal hybrid female parent for high-quality meat pigs [ 16 ]. Based on previous work, we investigated the runs of homozygosity (ROH) and copy number variations (CNVs) of AQ pigs, identifying a number of candidate genes associated with economic performance traits [ 13 ].…”
Section: Introductionmentioning
confidence: 99%